Analysis of the cornea donor data: an eye bank study - Tufekci, Ayse Balikci; Cevik, Sadik Gorkem; Parmak, Neslihan; Duman, Rahmi; Cevik, Mediha Tok; Kazanci, Burcu; Aslanci, Mehmet Emin; Yucel, Ersin (The European Research Journal, 2016)
Objectives. To analyse 1.5-year data of our newly established eye bank and to evaluate the factors affecting donor quality. Methods. Our bank’s donor cornea data between July 2013 and November 2014 were retrospectively analysed. The effects of donor age, sex, and time from death to harvesting on the findings of specular microscopy were assessed. Results. A total of 139 corneas retrieved from 70 donors. The mean age of donors was 34.2±14.6 (5-64) years. The mean time from death to harvesting was 6.7±2.9 (1-13) hours; the mean time from collection to transplantation was 5.2±2.8 (1-14) days. Age had a significant negative correlation with mean endothelial cell count (ECC), a significant positive correlation between mean cell area (MCA) and standard deviation (SD). Time from death to harvesting had a significant negative correlation with cell count and 6A; it had a significant positive correlation with SD, the coefficient of variation, and MCA. Conclusion. According to the results of the present study, ECC, MCA, and SD levels were greater in younger donors. Endothelial morphology was altered as the time from death to harvesting was prolonged; however, the alteration in cell morphology was not severe enough to alter transplantation success with the corneas being harvested within the first 13 hours.